Ketersediaan Pangan Dan Gizi Merupakan Faktor Pemungkin Lingkungan terhadap Penurunan Stunting di Kawasan Asia Terpilih: Analisis Data Neraca Bahan Makanan Badan Pangan Dunia (FAO Food Balance Sheets) - Jufran Juanda; Ratu Ayu Dewi Sartika; Diah Utari (Jurnal Kesehatan Komunitas, 2022)
Introduction, stunting interventions have not touched the basic determinant, namely the food system, which starts from the formation of food availability patterns at the national level. This study aims to find patterns of food availability and macronutrients that determine the prevalence of stunting in 23 Asian countries in 3 regions. Methods, Ecological study research design using secondary data from the Food Balances Sheet from the FAO Food Agency downloaded via the internet. Results, Availability of energy, protein, and fat in Southeast Asia and South Asia is lower than West Asia which has a stunting prevalence of <15%. The lower the availability of macronutrients, the higher the prevalence of stunting. In conclusion, the availability of food and macronutrients that are close to the proportion of healthy consumption patterns is an environmental enabler for stunting reduction.